Maritime Trade and the Formation of Economic Networks and Cultural Hybridity’s along the Medieval Silk Road - Ursula seventry, Maria; Nggada, Markus Talu; Leda, Adrianus Watu (Journal Social Humanity Perspective, 2023)
This paper questions the central role played by Mediterranean trade in shaping economic change and cultural exchange in the trade along the medieval Silk Road and specifies its relevance to management studies. A qualitative design as an inherent aspect of the study that includes the use of historical sources, archaeological research, and the semi-structured interview with the experts in the realm of maritime life and world-trading routes helped clarify that the exchange networks at sea were far more than a commodity exchange. They rebuilt governing structures, realigned institutional structures, and resorted to rearranging cultural structures along the seafaring settlements of the Silk Road. There are four interdependent dimensions namely; the economic integration, cultural syncretism, hybrid identities and strategic importance of the coastal ports and its related infrastructure. In maritime trade, significant aspects of decentralized coordination, flexible management approaches, and informal rules of regulation regulated the behavior of shippers, shipowners, and seafarers and act indicative of network governance in global supply chains today. These cultural interactions led to sharing of knowledge, religious tolerance and framing of commercial ethics that provided long term cooperations among heterogeneous societies. The cities of the port were both sources of economic growth and centers of cultural and institutional creativity according to the historical precedence location, infrastructure and human capital play. In brief, the study offers a historically rooted critique that undoes Eurocentric modes, and brings out alternative inter-culturally negotiated performances of institutional practice.